Therapeutic options for leukemic transformation in patients with myeloproliferative neoplasms. (December 2017) - Khan, Maliha; Siddiqi, Rabbia; Gangat, Naseema
Highlights: Supportive therapy, low-dose chemotherapy have unfavorable results in post-MPN AML. Hypomethylating agents may provide modest benefit to ASCT-ineligible patients. Induction chemotherapy alone improves response rates but does not prolong survival. Allogeneic stem cell transplantation has maximum curative potential. Induction chemotherapy plus ASCT should be the treatment goal for most patients. Abstract: Approximately 5–10% of patients with Philadelphia chromosome negative myeloproliferative neoplasms (MPN) comprising of essential thrombocythemia, polycythemia vera and primary myelofibrosis) experience transformation to acute myeloid leukemia (AML, ≥20% blasts). Treatment options for post-MPN AML patients are limited, as conventional approaches like standard chemotherapy, fail to offer long-term benefit. Median survival for secondary AML is ∼2.4 months. Post-MPN AML therefore represents an area of urgent clinical need. At present, allogeneic stem cell transplant (ASCT) following induction therapy is the best therapeutic option. Patients ineligible for ASCT are treated with hypomethylating agents. New agents under investigation include histone deacetylase inhibitors, JAKinhibitors and agents targeting the BRD4 protein. Combined treatment strategies involving these novel agents are being tested. In this review we present the current evidence regarding treatment options for post-MPN AML patients.